For the polynomial P (x) = 4x³ + cx² +x + 2 the value of c is -13.
Polynomial is an algebraic expression that has more than two terms. In other words, it is a combination of different variables with mathematical operations.
The given equation of polynomial is,
P (x) = 4x³ + cx² +x + 2 (1)
Since, When polynomial is divided by x-2, and x+1 it gives the same remainder,
This implies that at x=2 and x=-1, the value of the polynomial will be equal.
P(2)=P(-1)
4×(2)³+c(2)²+2+2=4×(-1)³+c(-1)²+(-1)+2
32+4c+4=-4+c+1
3c=-3-36
3c=-39
c=-13
So, the value of c is -13.
To know more about Polynomial on:
#SPJ3
Answer:
Step-by-step explanation:I don't say you have to mark my ans as brainliest but if you think it has really helped you please don't forget to thank me ...
(16, 15), (13, 10)
(0, 7), (3, 10)
(11, 13), (8, 18)
Answer: Rate of Change and Slope Quick Check
C. -1/3
D. (11,13) (8,18)
B. -2
D. Undefined
D. 55/1
Step-by-step explanation:
Answer:
i got 3
Step-by-step explanation:
Answer: c 17.9°
Step-by-step explanation:
Answer:
the answer is c
Step-by-step explanation:
I took the test
How do you solve this equation?
To find the vertical asymptotic equations of the rational function, we must first find the points of intersection of the function with the x-axis. These points are the solutions of the equation f(x) = 0. We decompose the exponential function into the product of two expressions: f(x) = (x² + 9x)(x² - 2x - 15) Now we can set each of the expressions inside the parentheses equal to zero and solve the vertical asymptotic equations: x² + 9x = 0 or x² - 2x - 15 = 0 To solve the first equation, we can factor x out: x(x + 9) = 0 So the two vertical asymptote equations are x = 0 and x + 9 = 0 (that is, x = -9). To solve the second equation, we can use the analysis method or the quadratic formula. Using the analysis method, we can decompose the expression x² - 2x - 15 in the following form: (x - 5)(x + 3) = 0 Therefore, two vertical asymptote equations equal to x - 5 = 0 (that is, x = 5) and x + 3 = 0 (that is, x = -3). So the vertical asymptotic equations of the rational function f(x) = (x² + 9x)(x² - 2x - 15) are equal to x = 0, x = -9, x = 5 and x = -3.